High mobility group box 1 prolongs inflammation and worsens disease in pneumococcal meningitis - Höhne, Christopher; Wenzel, Michael; Angele, Barbara; Hammerschmidt, Sven; Häcker, Hans; Klein, Matthias; Bierhaus, Angelika; Sperandio, Markus; Pfister, Hans-Walter; Koedel, Uwe (Brain, 2013)
Neutrophilic inflammation, which often persists over days despite appropriate antibiotic therapy, contributes substantially to brain damage in bacterial meningitis. We hypothesized that persistent inflammation is the consequence of a vicious cycle in which inflammation-induced cell injury leads to the release of endogenous danger molecules (e.g. high mobility group box 1) that drive the inflammatory response, causing further damage. The present study aimed to assess the mechanisms of high mobility group box 1 protein release and its functional relevance for the development and progression of pneumococcal meningitis. High mobility group box 1 was found in large quantities in cerebrospinal fluid samples of patients and mice with pneumococcal meningitis (predominantly in advanced stages of the disease). By using macrophages, we demonstrated that the release of high mobility group box 1 from macrophages following pneumococcal challenge is passive in nature and probably not connected with inflammasome- and oxidative stress-dependent inflammatory cell death forms. In a mouse meningitis model, treatment with the high mobility group box 1 antagonists ethyl pyruvate or Box A protein had no effect on the development of meningitis, but led to better resolution of inflammation during antibiotic therapy, which was accompanied by reduced brain pathology and better disease outcome. Additional experiments using gene-deficient mice and murine neutrophils provided evidence that high mobility group box 1 acts as a chemoattractant for neutrophils in a receptor for advanced glycosylation end products-dependent fashion. In conclusion, the present study implicated high mobility group box 1, likely released from dying cells, as a central propagator of inflammation in pneumococcal meningitis. Because persistent inflammation contributes to meningitis-associated brain damage, high mobility group box 1 may represent a promising target for adjunctive therapy of this disease.
Gesehen am 02.01.2022